Agricultura familiar e desenvolvimento rural: um olhar a partir dos núcleos de agricultores familiares no município de Mata - RS - Piber, Roselaine Tereza (2021)
The dissertation presents a study on the Family Farmers Nucleus (NAFs), constituted in five rural agglomerates in the Municipality of Mata-RS. The research aims to analyze the existence of Family Farmers Nucleus as an experience of organizing family farming in the Municipality of Mata, over time, in order to know and explain their role in the development of the Municipality. With a qualitative methodological approach, in a participatory perspective, the chosen data collection instrument was the semi-structured interview: five face-to-face interviews, one with each of the leaders of five family farmer nuclei, during the second half of 2020. As well as dialogues and interviews with nine (9) other actors in the municipality and document analysis (book of minutes from four cores). The methodology used to interpret the collected data can be considered as content analysis, both for documents and interviews. In addition, data from the Brazilian Institute of Geography and Statistics (IBGE), Agricultural Census 1970-2017, was used to incorporate into the study some dynamics of Family Farming in the Municipality. The dissertation text consists of an introduction, three thematic chapters and final considerations. The first chapter deals with the theoretical framework and addresses the socio-historical process of formation of family farming in the municipality of Mata RS. The second is organized into three sections, which present experiences of collective organization in rural areas, Local institutions and their relationship with the NAFs, the socio-political context during their institution and the Agricultural Patrol Project. The third makes an effort to understand the role of NAFS in the dynamics of family farming and the meaning of rural development expressed in the minutes and speeches of the interviewees, their collective actions and demands, as well as the challenges and opportunities for local development and the role of family farmer nuclei in this context. This research concludes that the NAFs played a fundamental role in the productive dynamics and collective processes of family production units, in the joint search for problem solving to improve quality of life and social reproduction. Therefore, they can be recognized as a social place for the collective construction of alternatives that promote development.